Jenis, Intensitas Infestasi, dan Prevalensi Ektoparasit pada Kucing Kampung (Felis Catus Linnaeus, 1758) di Kecamatan Cisata, Kabupaten Pandeglang, Banten - Iryana, Irfan; Bila, Bela Salsa; Rahmawati, Dania; Maulana, Alfin; Reffi, Mochamad; Abdilah, Nurullah Asep (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Ectoparasites of domestic cats (Felis catus) are of both veterinary and public health concern due to their role as zoonotic agents and disease vectors. This study investigated the diversity, infestation intensity, and prevalence of ectoparasites in domestic cats from Cisata District, Pandeglang, Banten, Indonesia. A total of 824 ectoparasites were collected from 37 cats captured in three villages. Morphological identification revealed three species: Felicola subrostratus, Ctenocephalides felis, and Haemaphysalis sp. Overall infestation intensity and prevalence were categorized as moderate, except for C. felis in male cats (light infestation) and F. subrostratus in females (common prevalence). These findings emphasize the need for preventive and control measures to reduce the zoonotic risks associated with feline ectoparasites.